(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The liver is the largest internal organ of the human body and plays a central role in metabolism, detoxification, bile production, and immune regulation. Understanding its detailed anatomy, including segmental structure, vascular architecture, and biliary pathways, is essential for modern hepatobiliary surgery. This article provides an overview of the macroscopic and microscopic anatomy of the liver and discusses its clinical and surgical significance in procedures such as hepatic resection, liver transplantation, and minimally invasive hepatobiliary interventions.